6-(1x+10)=42

Simple and best practice solution for 6-(1x+10)=42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6-(1x+10)=42 equation:


Simplifying
6 + -1(1x + 10) = 42

Reorder the terms:
6 + -1(10 + 1x) = 42
6 + (10 * -1 + 1x * -1) = 42
6 + (-10 + -1x) = 42

Combine like terms: 6 + -10 = -4
-4 + -1x = 42

Solving
-4 + -1x = 42

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -1x = 42 + 4

Combine like terms: -4 + 4 = 0
0 + -1x = 42 + 4
-1x = 42 + 4

Combine like terms: 42 + 4 = 46
-1x = 46

Divide each side by '-1'.
x = -46

Simplifying
x = -46

See similar equations:

| 10s= | | 6(8-t)+11=-11(t-4)-7 | | 15-x=6x | | 4x^2+7x-92=0 | | 4-4x^2-4y^2+8xy=0 | | 5s= | | 8x+3y=80 | | 2/7k-3/7=-19/8 | | -7y+13=223 | | 5+2y=48 | | 8x+5=8x-6 | | 8.9x+9-1.9x=2 | | 1/8x-2 | | p(3p+1)(3p-1)= | | 55+(2x-49)+90+x=180 | | 13c+40=ac-20+c | | 3x-(4x+9)=5x-45 | | 15x-13=9x-6 | | 8x-3=5+44 | | 2x^2-3x-170= | | 2x-49+55-90+x=180 | | 2w+2*(5+w)=150 | | 6+4[5-3(7+2)-6]= | | 7(2m-2)+2m+10= | | -47-(-95)= | | 2x-49+55=180 | | 2w+10=20 | | 54l+43.42=3605.26 | | s=-16t^2+80t+96 | | z=-2.10 | | 110x3/5 | | x^2+25+50=0 |

Equations solver categories